Hijaukan Laporan Keuangan: Praktik Akuntansi Berkelanjutan pada Kualitas Informasi Akuntansi Perusahaan Properti - Yusli Mariadi; Nungki Kartikasari; D Tialurra Della Nabila (Jurnal Ilmiah Akuntansi dan Humanika, 2026)
This study examines whether sustainability accounting practices among Indonesian listed property firms remain at the level of green claims or are supported by relevant, measurable, consistent, comparable, and verifiable information. A quantitative content analysis was conducted on 2025 corporate reports from 15 firms, producing 270 evidence-based pengodean decisions. Sustainability accounting practices cover environmental costs, green investment, energy and water, emissions and waste, and environmental risks. Information quality is assessed through relevance, quantification, consistency, comparability, and verifiability, while green asset certification is used as a grouping attribute. Six firms have defensible certification support, whereas nine lack qualifying final-certification evidence. Mean sustainability accounting scores are relatively close at 9.00 and 8.33, while the information-quality difference is larger at 9.83 and 8.89. None of the firms obtains asurans keberlanjutan independen. The findings indicate that certification is not a prerequisite for sustainability accounting practices, but may strengthen traceability and documentation discipline.